The Polish Constitutional Court And Political "Refolution" After 1989: Between the Continuity and Discontinuity of the Constitutional Narrative - Kustra-Rogatka, Aleksandra (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
The paper considers the issue of constitutional justice during political transition in Poland. The author states that regardless of the stage of the political transition, both the constitution-creators and the constitutional judiciary tend to distance themselves from the past. However, the absolute discontinuity of constitutional narration is impossible, since the remaining old constitutional environment affects the constitutional court’s jurisdiction, both in its merits and effects.In Poland the basic aspect of piecemeal constitutional continuity followed from the fact that principle of the democratic state ruled by law was introduced into the constitutional system as an amendment to the Constitution of 1952. On the levels of both constitutional and statutory law such continuity was also guaranteed (at least to some extent) by legal provisions regulating the Constitutional Tribunal’s competences and the effects of the Constitutional Tribunal’s judicial decisions (e.g. the Sejm’s right to overrule them). Yet, even after the entry into force of the new Constitution of 1997, the narrative of constitutional discontinuity did not (and could not) prevail in Poland. The new democratic State has had to cope with many salient post-transition constitutional issues that demanded taking into account the temporality of justice and thus - sometimes – giving priority to aspects of legal continuity. Some of them regarded so called “legal survivals” of the old regime, others were linked to the idea of transitional justice.Judicial decisions of the Polish Constitutional Tribunal presented in this paper demonstrate the “refolutional” character of most political transitions.
Keywords: sprawiedliwość okresu przejściowego; kontrola sądowa; Trybunał Konstytucyjny; rządy prawa; przemiany polityczne